Exploring the efficacy of Malay silat as a vehicle for positive youth development in Malaysia - Abdul Khalid, Nurliza; Krauss, Steven Eric; Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Critical analysis of a wide range of research findings unravels the opposing views that have long been subject of discussion and contention pertaining to the efficacy of martial arts as a vehicle for positive youth development. Review of past and present literatures has highlighted the abundance of benefits associated with martial arts among youth, especially in terms of enhancement of physical health, self-esteem and general improvement in academic achievement. On the other hand, some researchers differ radically as they dismiss the positive benefits of martial arts as something that have not been comprehensively or conclusively researched. An overwhelming amount of attention has also been given to researching the efficacy of specific and non-specific martial arts; i.e. traditional or contemporary martial arts in dealing with youth at risk. Along these lines, scant research has been conducted on the efficacy of a specific Malay martial arts known as ‘Silat’ as a vehicle for positive youth development. Little is known about the extent of how this particular martial art can be used to promote positive, tangible developmental outcomes. The limited research in this area presents a risk such that if palpable conclusions regarding the efficacy of Silat cannot be made known to policy makers, the legendary art of Malay Silat stands to lose its historical significance, lineage and prominence in Malaysia. This review thus aims to explore the efficacy of martial arts -- and Malay Silat in particular – in promoting positive youth development.